2002
DOI: 10.1590/s1413-86702002000400007
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon vancomycin: induced side effects

Abstract: Vancomycin has been used with increased frequency during the past 15 years and the most common toxicity with this drug is the red man syndrome . Other adverse effects include neutropenia, fever, phlebitis, nephrotoxicity, ototoxicity, thrombocytopenia, interstitial nephritis, lacrimation, linear IgA bullous dermatosis, necrotizing cutaneous vasculitis and toxic epidermal necrolysis. Only two cases of vancomycin-induced Stevens-Johnson syndrome and one case of pancytopenia have been reported in the medical lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
2
11

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(44 citation statements)
references
References 9 publications
(19 reference statements)
2
27
2
11
Order By: Relevance
“…Recently, Bay et al [7] described a child treated with vancomycin for pneumonia caused by S. aureus who developed vancomycin-induced thrombocytopenia. On the other hand, Rocha et al [8] suggested that linezolid and streptogramins might be alternatives whenever vancomycin was the treatment of choice if the patient presented serious adverse events. However, Kohno et al [9] observed that hematological adverse events were more frequent with linezolid, although reversible.…”
Section: Commentmentioning
confidence: 99%
“…Recently, Bay et al [7] described a child treated with vancomycin for pneumonia caused by S. aureus who developed vancomycin-induced thrombocytopenia. On the other hand, Rocha et al [8] suggested that linezolid and streptogramins might be alternatives whenever vancomycin was the treatment of choice if the patient presented serious adverse events. However, Kohno et al [9] observed that hematological adverse events were more frequent with linezolid, although reversible.…”
Section: Commentmentioning
confidence: 99%
“…The possible mechanisms include marrow suppression, sequestration, and peripheral destruction. Some authors argue against bone marrow suppression owing to bone marrow biopsy findings, which have shown both hypoplasia and hyperplasia of the granulocyte series (5) . However, evidence that supports an immunological etiology also exists.…”
Section: Case Reportmentioning
confidence: 99%
“…For this, the present clinical guide recommends maintaining the minimal concentration (Cmin), determined at the end of administration interval, at a therapeutic range of 5 and 10 µg/ml, and maximum concentration (Cmax), determined 3 h after intravenous administration, at not more than 40 µg/ml. Apart from RMS, other principal adverse reactions of vancomycin include ototoxicity, nephrotoxicity, and phlebitis (Rocha et al, 2002).…”
Section: Vancomycin and Risk Factors For Hypersensitivity Reaction Dementioning
confidence: 99%